NEED ASSESSMENT OF SOCIAL SKILLS TRAINING PROGRAM FOR SPECIAL STUDENTS - Quratul Ain Hina; Uzma Mazhar; Syeda Rida Zahra (JIE, 2025)
The study was conducted with the objectives assess the need of special students regarding social skills, to compare the social skills of special students on the basis of gender and to develop a social skill training program for special students. The Theoretical framework of the study was based on the Social Skills Parameters by Aderson. (2013) consisted of three main components (social play, emotional regulation and communication skills). The researcher used a quantitative approach and descriptive design for the study. The population consisted of 1177 special students enrolled in Sir Syed School, College of Special Education Rawalpindi, and Global Special School Rawalpindi for session 2024. Proportionate sampling techniques were used for research. The sample size of the study was (n=40) special students. The researcher adapted an observation checklist for data collection in the light of Anderson (2013). The researchers visited the schools and observed the student from one month continually. The data was analyzed by applying Mean and t-test. The study was delimited to four types of special children (autism, hearing impairment, muteness, and attention deficit hyperactivity disorder). Further it focused on students enrolled in special education programs between the ages of 5 and 10. The results emphasized that there was a need for specialized social skills programs that can enhance peer interactions, communication, emotional control, and adaptive abilities as understanding emotional flexibility, verbal and non-verbal conversational skills specially. It was also revealed that there was statistically significant difference found between male and female students. The male students were found somehow better than female students. It was recommended to guarantee consistent skill development and real-world application across educational contexts, it was suggested to put in place a standardized, personalized social skills training program with interactive exercises catered to each student's needs and follow-up sessions